2007 22nd International Congress on Instrumentation in Aerospace Simulation Facilities 2007
DOI: 10.1109/iciasf.2007.4380890
|View full text |Cite
|
Sign up to set email alerts
|

Filtered Rayleigh Scattering-Based Concentration Measurements for a Horizontal Buoyant Jet

Abstract: Filtered Rayleigh Scattering (FRS) is a nonintrusive technique which is used to study a variety of flowfields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In fact, we found that both the transversal velocities u and v have the same scale d 1=2 W 0 in the core region, applying Eq. (12) to the case shown in Figure 8, we get d 1=2 $ 0.05 that is of the order of magnitude of what is shown if the figure. This give the experimental evidence that the flow is not axi-symmetric at the nozzle exit and the set up of high fidelity simulations of a horizontal buoyant jet cannot ignore the flow recirculations upstream the release section.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…In fact, we found that both the transversal velocities u and v have the same scale d 1=2 W 0 in the core region, applying Eq. (12) to the case shown in Figure 8, we get d 1=2 $ 0.05 that is of the order of magnitude of what is shown if the figure. This give the experimental evidence that the flow is not axi-symmetric at the nozzle exit and the set up of high fidelity simulations of a horizontal buoyant jet cannot ignore the flow recirculations upstream the release section.…”
Section: Resultssupporting
confidence: 50%
“…This core deformation has already been observed by McGaha and Reeder. 12 In jets in a crossflow, the shear of the ambient wind on the body of the jets causes a similar deformation of the flow. 13 Due to the initially thin boundary layer around uniform potential core, well-defined vortical structures are observed close to the nozzle.…”
Section: Resultsmentioning
confidence: 99%
“…By far the most common filter/laser pairing is a molecular iodine filter and an Nd:YAG laser (532 nm). Iodine can also be used as the absorbing species for a CW argon-ion laser (514.5 nm) illumination source, as was demonstrated by Komine et al in their initial Doppler global velocimetry (DGV) measurements [72], and utilized for FRS by Reeder et al [73,74]. As mentioned previously, the intensity of Rayleigh scattered light scales with 1/λ 4 , so the strength of the Rayleigh scattered signal greatly increases when using a UV illumination source [8].…”
Section: Absorption Filtermentioning
confidence: 94%
“…This is generally accomplished when the variation in a calibrated and normalized FRS signal is a function only of the local mixture composition. Reeder et al [73,74] designed such an experiment and used FRS to quantify the core jet trajectory and mixing rate of buoyant helium and carbon dioxide jets issuing into air using a CW laser. They identified jet features that influence the gross mixing rate, such as side jets that expel fluid from the core.…”
Section: Mixture Compositionmentioning
confidence: 99%